Left Atrial Function Post Radiofrequency and Cryoballoon Ablation Assessed by Volume-Pressure Loops - Karanasos, Antonios; Tyrovolas, Konstantinos; Tsiachris, Dimitrios; Efremidis, Michalis; Kordalis, Athanasios; Karmpalioti, Maria; Prappa, Efstathia; Karagiannis, Stefanos; Aggeli, Constantina; Gatzoulis, Konstantinos; Tousoulis, Dimitrios; Tsioufis, Costas; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Left atrial (LA) function is linked to atrial fibrillation (AF) pathogenesis. AF catheter ablation decreases disease burden with potentially favorable effects on cardiac function. Atrial volume-pressure loops can optimally assess the LA function. Objective To investigate changes in LA function by volume-pressure loops after paroxysmal AF ablation and explored potential differences between the radiofrequency and cryoballoon ablation. Methods We analyzed 44 patients undergoing paroxysmal AF ablation from 2 centers, 22 treated with radiofrequency and 22 with cryoablation. Pre- and post-procedure, all patients underwent a real-time three-dimensional transthoracic ECG to evaluate LA volume, while simultaneously recording LA pressure following transseptal puncture. Volume-pressure loops pre- and post-procedure were created by paired data. Areas of A-loop (LA booster pump function) and V-loop (LA reservoir function), and the stiffness constant determining the slope of the exponential curve during LA filling were calculated. Results Average LA pressure, A-wave amplitude, and V-wave amplitude were increased post-procedurally (p < 0.001). Overall, A-loop area decreased (p = 0.001) and V-loop area tended to increase (p = 0.07). The change in both A-loop and V-loop areas was similar between radiofrequency- and cryoballoon-treated patients (p = 0.18 and p = 0.52, respectively). However, compared with cryoballoon-treated patients, radiofrequency-treated patients had higher increase in the stiffness constant (b = 0.059; 95% CI: 0.022–0.096; p = 0.006). Conclusion AF catheter ablation by the radiofrequency or cryoballoon is associated with the decrease of the booster pump function and increase of the reservoir function. Moreover, there is a post-procedural increase of LA pressure which is associated with an acute increase in LA stiffness in radiofrequency ablation, but not in cryoablation.